The influence of hydroquinone on tyrosinase kinetics. - Stratford, MR; Ramsden, C; Riley, P (2012)
In vitro studies, using combined spectrophotometry and oximetry together with hplc/ms examination of the products of tyrosinase action demonstrate that hydroquinone is not a primary substrate for the enzyme but is vicariously oxidised by a redox exchange mechanism in the presence of either catechol, L-3,4-dihydroxyphenylalanine or 4-ethylphenol. Secondary addition products formed in the presence of hydroquinone are shown to stimulate, rather than inhibit, the kinetics of substrate oxidation.